Plant Growth Analysis of Maize (Zea mays): Impact of Second Paclobutrazol Application Timing - Syafrizal, Yusril; Wahyuningsih, Gendro Indri; Ulfah, Fajarani; Pratama, Ananta Bayu; Adileksana, Cahyo (P3M Politeknik Negeri Jember, 2025)
Maize is a vital source of carbohydrates and livestock feed in Indonesia, where domestic demand is rising despite inconsistent productivity. Innovative cultivation methods, such as paclobutrazol (PBZ) application, are being explored to boost maize productivity. PBZ affects maize's growth, with its effectiveness depending on the timing of application. This study was to figure out the optimal timing of PBZ application to improve the synchronization of cob and female flower emergence, thereby maximizing plant growth and yield. The experiment utilized a randomized complete block design (RCBD) comprising five treatments: a control and four intervals for the second PBZ application (3, 6, 9, and 12 days after the first application), each replicated three times. Data were analysed using Analysis of Variance (ANOVA) at a 5% significant threshold, succeeded by Tukey’s test. Results showed that the timing of the second PBZ application significantly influenced maize growth and yield. A three-day interval after the first PBZ application produced the highest values in key morphological variables, such as green leaf index and total dry weight. This timing also optimized plant growth metrics, leading to higher maize yield. In conclusion, a three-day interval is recommended for maximizing maize productivity.